A Novel Trihybrid Material Based on Renewables: An Efficient Recyclable Heterogeneous Catalyst for C−C Coupling and Reduction Reactions. Issue 17 (11th August 2016) - Majumdar, Rakhi; Tantayanon, Supawan; Gopal Bag, Braja
Abstract: The generation of organic–inorganic hybrid materials from renewable resources and their utilization in basic and applied areas has been at the forefront of research in recent years for sustainable development. Herein, a novel organic–inorganic trihybrid material was synthesized by in situ generation of palladium nanoparticles (PdNPs) in a hybrid gel matrix based on renewable chemicals. Constituents of the hybrid gel included a pentacyclic triterpenoid arjunolic acid extractable from Terminalia arjuna and the leaf extract of Chrysophyllum cainito rich in flavonoids. We took advantage of the presence of flavonoid molecules in this hybrid gel to generate an advanced trihybrid gel through in situ reduction of doped Pd II salts to stable PdNPs. The xerogel of this trihybrid material was used as a recyclable heterogeneous catalyst for C−C coupling and reduction reactions in aqueous media. We also demonstrated that the in situ generated PdNPs containing trihybrid material was a more efficient catalyst than the trihybrid material generated with presynthesized PdNPs. Abstract : Waste not, want not : On the basis of renewable chemicals, an organic–inorganic trihybrid material is synthesized by in situ generation of Pd nanoparticles (PdNPs) in a hybrid gel matrix. The xerogel of this material is used as a recyclable heterogeneous catalyst for C−C coupling and reduction reactions in aqueous media. The catalyst prepared from the in situ generated PdNPs is more efficient than the catalyst generated with presynthesized PdNPs.